From Riggs to World Bank: Recurring themes in study of development administration - Walker, Judith-Ann (1996)
Focussing on the riddle of identifying the factors that explain public bureaucracies' ability to attain developmental goals, the author discusses Fred Riggs and his CAG's attempt to formulate the problem but failure to answer it, followed by incursions of scholars from other fields, and the World Bank's current Development Administration agenda under its neo-liberal paradigm. She argues that the way forward in the search lies in distilling recurring themes from amongst disparate contributions in the field, taking cognisance of the discipline's two vital distinctions, i.e., political environment versus internal organisation, and growth versus change. The author identifies the recurring themes in two sets of variables- administrative capacity building and autonomy, and decentralisation and bureaucratic politics. - Reproduced
Keywords: Development policy; Development administration - India; Development administration